Creatures of attention : aesthetics and the subject before Kant - Wankhammer, Johannes, 1982- (Signale (Ithaca, N.Y.), 2024)
"The book examines the discourse on attention emerging in the European Enlightenment (1650-1780) with a focus on German philosophy and literature. It argues that this discourse influenced the formation of aesthetic philosophy in the eighteenth century. Notable figures discussed include René Descartes, G.W.F. Leibniz, Christian Wolff, and Alexander Baumgarten."--